Digitoxigenin-3-O-β-D-Glucopyranoside from The Roots of Sapium sebiferum - Bose, Chandana (Asian Journal of Chemistry, 2010)
The plant Sapium sebiferum is commonly known as Vilayati shisham in Hindi and belongs to natural order Euphorbiaceae. The plant is widely cultivated in India. The ethyl acetate soluble fraction of the concentrated ethyl alcohol soluble part of its roots when subjected to column chromatography yielded a yellow coloured compound, m.f. C29H44O9, m.p. 200-201 ºC [α]D -19.3º, M+ = 536, which on various chemical degradations, colour reactions and spectral analysis was identified as digitoxigenin-3-O-β-D-glucopyranoside AC-4.